If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 13y = 4620 Solving 10x + 13y = 4620 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13y' to each side of the equation. 10x + 13y + -13y = 4620 + -13y Combine like terms: 13y + -13y = 0 10x + 0 = 4620 + -13y 10x = 4620 + -13y Divide each side by '10'. x = 462 + -1.3y Simplifying x = 462 + -1.3y
| 7/5+1/4t=5 | | 5x^2-5x-910=0 | | 4+4i/6-3i | | 7b-8=5b+4 | | -10x-19=-209 | | s=2X^2-10X+50 | | 6s^2-11s=35 | | UC=2X^2-10X+50 | | 6s^2+11s=35 | | 3y-8=6y+28 | | 168.08=2.82w+14.9 | | 6(4y-1)=18y | | 7x-1+6x+2=2x+4 | | 2x+4=7x-1 | | 3(y+1)=5y+17 | | 2(5x-11)+7=3(x-7)-15 | | 1/4(5x-4)=3 | | -7x+7=9 | | 3.9x+5.37=-19.20 | | 7-18=z/-5 | | .3(6)+.05x=.15(36+x) | | x(.1)+x=210000 | | 2.8(1+0.5x)=-7 | | x(.1)+x=262500 | | y=pc | | 262500=x+x(.1) | | 5(3x-7)-14x=8 | | 8m+14m=198 | | -13=3+4y | | -(4y+2)-(-3y-6)=-3 | | -(4y+2)-(3y-6)=-3 | | 6(a-7)+18=3(a-4) |